Research on the suitability and spatial and temporal evolution of innovation environment niche suitability of regional innovation ecosystem under digitalization - He, Zitong; Wang, Haijun; Ma, Xiaolin; Hu, Yuhan; Zhao, Huiyan (Frontiers in Physics, 2024)
Regional innovation ecosystems (RIEs) are a new paradigm in innovation research, and the development of RIEs under digitization is constrained by the development of innovation environments. The study of ecological niche suitability of regional innovation environment provides the basis for the government to create an innovation environment suitable for the development of a regional innovation ecosystem. This paper conducts an empirical analysis based on panel data from 29 provinces (autonomous regions) in China from 2012 to 2021. The paper analyzes the suitability of the ecological niche of the innovation environment as well as the spatio-temporal evolution pattern of the regional innovation ecosystem under digitalization in China. The results of the study show that: (1) The innovation environment of regional innovation ecosystems under digitization in China has become increasingly suitable during the sample period. (2) From the perspective of evolution in time, the suitability of the ecological niche of the regional innovation environment has always maintained an evolutionary trend of rolling forward in the echelon. (3) From the perspective of spatial evolution, the center line of the curve of the development level of the suitability of the regional innovation environment shows a rightward shifting evolution.